An exploration of barriers, facilitators, and practical solutions for adopting medication synchronization into community pharmacies: A qualitative analysis - Tamera D. Hughes; Stacey Cutrell; Lana M. Minshew; Patrick Brown; Stefanie P. Ferreri (Elsevier, 2022)
Background: Community pharmacies across the nation have adopted medication synchronization (Med Sync) services with the aim of improving medication adherence. To help incorporate Med Sync into a pharmacy's workflow, pharmacy associations and organizations developed implementation guides for community pharmacies. However, considerable variability in the adoption of this service exists as pharmacies struggle to implement Med Sync into traditional workflow. Researchers identified early adopters of Med Sync who dispense majority of their prescriptions as part of a Med Sync program. An exploratory study was undertaken with the aim to reveal themes surrounding facilitators and barriers to adoption of Med Sync in community pharmacies. Objectives: The objective of this study was to explore the barriers and facilitators associated with Med Sync adoption in community pharmacies and generate practical solutions for service adoption. Methods Community pharmacies participating in the North Carolina's Community Pharmacy Enhanced Services Network (CPESNsm) who were early adopters of Med Sync and had greater than 50% of their prescription volume being dispensed as part of a Med Sync program were recruited to participate in semi-structured interviews. Interviews were conducted, recorded, and transcribed verbatim with representatives who led the adoption of Med Sync in their pharmacy. Inductive coding and summary analysis were used to analyze the interview data and determine themes associated with facilitators and barriers. Results: Analysis of the interviews revealed four key themes: program organization, staff engagement, patient engagement, and provider engagements for Med Sync adoption. Each of these themes had several sub-themes, contributing to facilitators and barriers to Med Sync adoption. Subthemes of program organization included having organizational infrastructure, including a pharmacy software system, a dedicated area, and a consistent enrollment process. Subthemes of staff engagement included having a team-based approach, job training, and staff incentives. Patient engagement's subthemes included communication, finances, health literacy, and transportation. Provider engagement resulted with subthemes including lack of communication and provider-pharmacist relationships. Conclusion: To ensure successful adoption of Med Sync into traditional workflow, community pharmacies should employ a multi-factorial approach that includes internal and external components to the community pharmacy. This study identified facilitators associated with successful Med Sync adoption such as adequate staff engagement and requisite program organization. Barriers hindering successful Med Sync adoption resulted from challenges with provider and patient engagement. This study also makes an important contribution by providing practical solutions to Med Sync adoption based on participant responses and identified themes and sub-themes.